2012
DOI: 10.1111/j.1365-2354.2012.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of medication errors with parenteral cytotoxic drugs

Abstract: Errors involving cytotoxic drugs have the potential of being fatal and should therefore be prevented. The objective of this article is to identify the characteristics of medication errors involving parenteral cytotoxic drugs in Sweden. A total of 60 cases reported to the national error reporting systems from 1996 to 2008 were reviewed. Classification was made to identify cytotoxic drugs involved, type of error, where the error occurred, error detection mechanism, and consequences for the patient. The most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 18 publications
2
28
0
1
Order By: Relevance
“…Incident reports offer a valuable bird's eye view of the events those working at the front line consider important for the safety of patients. Our analysis showed that medication safety incidents in paediatric oncology occurred in prescribing, dispensing, administration and monitoring tasks, consistent with those found in adult oncology and other clinical settings (Ferner & Aronson, , ; Fyhr & Akselsson, ; Schwappach & Wernli, ). However, they also occurred in other tasks, those related to care coordination, to the handling or storing of medications and to children or families handling medications.…”
Section: Discussionsupporting
confidence: 84%
“…Incident reports offer a valuable bird's eye view of the events those working at the front line consider important for the safety of patients. Our analysis showed that medication safety incidents in paediatric oncology occurred in prescribing, dispensing, administration and monitoring tasks, consistent with those found in adult oncology and other clinical settings (Ferner & Aronson, , ; Fyhr & Akselsson, ; Schwappach & Wernli, ). However, they also occurred in other tasks, those related to care coordination, to the handling or storing of medications and to children or families handling medications.…”
Section: Discussionsupporting
confidence: 84%
“…On the other hand, MEs and subsequent PIs related to drug preparation might be recorded directly in the documents linked to the production process and/or elsewhere in the central pharmacy within a quality‐assured process. Nevertheless, it is well known that prescribing errors and subsequent PIs also exist in the group of cytotoxic drugs . Furthermore, because ward‐based clinical pharmacists are not yet established and accepted nationwide in Germany, the need for documentation of their work is of high priority—but is not obligatory—to demonstrate the additional value.…”
Section: Discussionmentioning
confidence: 99%
“…In this instance, a 43‐year‐old patient received a 5250‐mg dose of 5‐FU over 4 hours instead of the intended 4 days and died 22 days later from toxicity even after aggressive supportive care. Accidental overdoses with 5‐FU continue to be a significant problem …”
Section: Introductionmentioning
confidence: 99%
“…Accidental overdoses with 5-FU continue to be a significant problem. [2][3][4][5] Capecitabine is an orally bioavailable prodrug that is converted by 3 sequential enzymatic steps to yield 5-FU. 6 The most common toxicities caused by both agents are consequences of cytotoxic damage to rapidly dividing cells, and they include mucositis, diarrhea, and cytopenias.…”
Section: Introductionmentioning
confidence: 99%